IMS 4112 and VLP of HBV as Th1 Adjuvants for a Recombinant Protein of HIV-1 - Ingrid Rodríguez-Alonso; Daymir García; Emma Brown; Stephane Ascarateil; Enrique Iglesias (Journal of Vaccines and Immunology - Peertechz Publications, 2016)
Background: Current thinking suggests that vaccination approaches against the HIV-1should be directed to elicit a Th1 cell-mediated immunity, neutralizing antibodies and/or ADCC mediating antibody responses. Also, experimental evidences suggest that both the systemic and mucosal compartments of the immune system must be stimulated to achieve protection. In this regard, effective adjuvants are necessary. Thus, we developed the multiantigenic vaccine candidate TERAVAC that comprise the recombinant protein CR3 of HIV-1 and the surface (S) and core (C) virus like particles (VLP) of Hepatitis B virus (HBV) as adjuvant to promote a Th1 immune response. On the other side, the new Th1 adjuvant Montanide® IMS 4112 (IMS 4112), an oil-in-water micro-emulsion was developed by SEPPIC  Purpose of study: The aim of this work was to compare the adjuvant effect of IMS 4112 versus HBV VLP on the CR3(HIV-1)-specifi c immune response in Balb/c mice using schedules that combine nasal and/or subcutaneous inoculations. Results: We found a better Th1 response with HBV VLP but a higher IgG response in vagina with IMS 4112 after i.n. inoculation. In s.c. immunization similar immune responses were detected using both adjuvants. When combining i.n. and s.c. coadministration, the HBV VLP seemed to require less immunization doses to achieve detectable proliferation of CD4+ and CD8+ lymphocytes in the systemic compartment. Conclusion: Overall, HBV VLP seem to be a better adjuvant for the recombinant CR3 protein of HIV-1 than the IMS 4112 at the concentration it was used in this study.